IMPLEMENTASI PEMBELAJARAN DARING PADA MATA PELAJARAN AL-QUR'AN HADITS - Ahmad Izzul Widad Fahmi Fahmi; Evi Fatimatur Rusydiyah (JP : JURNAL PENDIDIKAN, 2021)
Learning the Qur'an and Hadith (in general) is a compulsory subject at every level of Madrasah educational institution, from Ibtidaiyah to Aliyah levels. The purpose of learning Al-Qur'an Hadith in Madrasas is so that students are able to read, write, memorize, interpret, understand, and skillfully carry out the contents of the Al-Qur'an Hadith in everyday life so that they become people who believe and fear Allah SWT. However, the learning that is currently being implemented is distance learning (PJJ) due to the large-scale social restrictions (PSBB). The PSBB was imple-mented due to the outbreak of the Corona Virus Disease 2019 (COVID-19). E-learning is the right learning model to overcome learning during a pandemic without face-to-face learning at school. To support e-learning learning, effective technology-based learning media are used, namely e-learning at MAN 3 Jombang, Zoom and Silacak, which can be easily accessed via Android.Keywords: Online Learning, Pandemic, the Qur'an and Hadith Learning